A chemical study of some active secondary metabolites in Spartium Junecum L. - سلامه, ريم; محفوض, رهف (Latakia University Journal -Medical Sciences Series, 2021)
This study was conducted on Spartium Junecum L.; a medicinal plant belongs to Fabaceae family. Plant samples (flowers and fruits) were collected from the countryside of Lattakia in 2019. The phenolic and flavonoids compounds were extracted from the dry flowers, then the total content was determined spectrophotometrically using the Folin-Ciocalteu and ALCL3 methods for phenolic and flavonoids compounds, respectively. Quinolizidine alkaloid were extracted from dry flowers and seeds and the presence of some alkaloids, such as: Cytisine, N-methylcytisine, Anagyrine, and Sparteine was investigating ​​using Thin-layer chromatography technique (TLC) and basing on the reference values ​​of the Retardation Factor (RF) of these alkaloids determined by using the same mobile phase applied in the references studies. The results showed that the yield of total phenolic content was (7.45 mg Gallic ac.E/g d.w) and (0.715 mg R.E/g d.w) for flavonoids. The flowers extract showed two spots on the TLC plate with Wagner's reagent, their RF values were 0.29 and 0.59, respectively, and these values are very close to the corresponding reference RF values​of cytisine and N-methylcysteine which are 0.28 and 0.61, respectively. The use of the vanillin reagent on the TLC plate showed the presence of a large number of spots (about 12 spots) of which two spots had RF values ​​very close to the reference ones of cytisine and N-methylcysteine. As for the seeds extract, two spots were shown when Wagner's reagent was applied. Their RF values ​​were 0.3 and 0.58, respectively, which in turn were very close to the corresponding reference values of cytisine and N-methylcysteine. While a large number of spots (about 7 spots) were appeared when the vanillin reagent was applied, two of them were close to the reference values of cytisine and N-methylcysteine. We can tentatively assume that the flowers and seeds extracts contain Cytisine and N-methylcytisine, while Anagyrine and Sparteine were not detected by the adopted analytical method.